Feeding habits of the cockfish, Callorhinchus callorynchus (Holocephali: Callorhinchidae) from off northern Argentina - Román, Jorge Martín (2020)
The feeding habits of Callorhinchus callorynchus were investigated in coastal waters off northern Argentina. The effect of body size, seasons and regions was evaluated on female diet composition using a multiple-hypothesis modelling approach. Callorhinchus callorynchus fed mainly on bivalves (55.61% PSIRI), followed by brachyuran crabs (10.62% PSIRI) and isopods (10.13% PSIRI). Callorhinchus callorynchus females showed changes in the diet composition with increasing body size and also between seasons and regions. Further, this species is able to consume larger bivalves as it grows. Trophic level was 3.15, characterizing it as a secondary consumer. We conclude that C. callorynchus showed a behavior of crushing hard prey, mainly on bivalves, brachyuran, gastropods and anomuran crabs. Females of this species shift their diet with increasing body size and in response to seasonal and regional changes in prey abundance or distribution.